Nannobiostratigraphy of Serikagni Formation in Southern limb of Sinjar anticline, Northwestern Iraq - Al-Hadeedy, Mahfoudh Abdulla; Al-Badrani, Omar Ahmed (Iraqi Journal of Science, 2024)
Investigations of calcareous nannofossils were done on the Serikagni Formation in the southern limb of the Sinjar anticline northwest of Iraq, specifics of the identification process's investigation (18 species of calcareous nannofossils belonging to 10 genera). Two biozones were proposed in this study based on their stratigraphic distribution, and they are as follows: Triquetrorhabdulus carinatus partial range Biozone CN1 and Sphenolithus belemnos Interval Biozone CN2. Correlation with other calcareous nannofossil biozones from regional schemes led to the conclusion that the Serikagni Formation's age is Early Miocene (Aquitanian)in the studied sections. It can conclude from higher speciation for calcareous nannofossils that the bloom at the Miocene because of increased temperature impacts climate change on the warm ocean's ecosystem.